Preserving the Role of the Audiologist in a Clinical Technology, Consumer Channel, Clinical Service Model of Hearing Healthcare - Abrams, Harvey B.; Singh, Jasleen (Seminars in Hearing, 2023)
The past decade has been characterized by significant changes in the distribution and sale of hearing aids. Alternatives to the clinical technology, clinical channel, clinical service (i.e., traditional) hearing healthcare delivery model have been driven by growth in hearing aid dispensaries housed in large retail establishments and direct-to-consumer hearing aid sales by internet-based companies unaffiliated with major hearing aid manufacturers (e.g., Eargo). These developments have been accompanied by acceleration in the growth of teleaudiology services as a direct result of the COVID-19 pandemic. The resulting development of nontraditional hearing aid distribution and sales models can be categorized into distinct archetypes as reviewed earlier in this publication. This article will review the Clinical Technology–Consumer Channel–Clinical Service model as exemplified by Jabra Enhance. We will describe a completely digital model of hearing aid distribution and sales that maintains the professional service component throughout the client journey to include an online tone test, the use of a risk mitigation questionnaire, virtual consultations, remote hearing aid adjustments, and the establishment and monitoring of client-centered treatment goals. Furthermore, this article will review the Jabra Enhance model within the context of consumer healthcare decision-making theory with a focus on the Consumer Decision-Making Model.
Keywords: hearing aids; teleaudiology; online hearing test; Consumer Decision-Making Model